Pelatihan Digital Marketing Menggunakan Media Brandmark Untuk Usaha Rumah Tangga di Era Revolusi Industri 5.0 di Kecamatan Semanding - Ulfa Yuliasari; Mario Fahmi Syahrial; Estri Purwani Rahayu; Ifa Ristia Sandra E; Riska Andriani; Rista Dwi Permata (CV SWA Anugerah, 2023)
One of the important keys in facing the Industrial Revolution Era 5.0 in home businesses is that it is characterized by technological integrity and artificial intelligence. Semanding District, as part of the community affected by this global transformation, needs to prepare household business actors with comprehensive digital marketing skills. This service aims to design and implement a digital marketing training program that focuses on specific needs, namely promotion of home businesses in Semanding District by learning logo or brand design so that the products that manufacturers offer are more easily remembered by consumers. With this digital marketing training, the products offered by UMKM (Micro small and Medium Enterprises) household businesses will be more practical, fast, efficient and easily delivered to consumers at relatively low costs because currently the concept of digital marketing is not only done via the web but is done with the role of social media. which makes it very easy for manufacturers to do. To strengthen the digital marketing capacity of household business actors, it is hoped that it can spur local economic growth, increase competitiveness, and strengthen economic resilience in Semanding District in the midst of the Industrial Revolution 5.0 era.